2022
DOI: 10.3390/molecules27092803
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Ruthenium Cyclopentadienyl Complexes Bearing Succinimidato and Phthalimidato Ligands

Abstract: In these studies, we investigated the antioxidant activity of three ruthenium cyclopentadienyl complexes bearing different imidato ligands: (η5-cyclopentadienyl)Ru(CO)2-N-methoxysuccinimidato (1), (η5-cyclopentadienyl)Ru(CO)2-N-ethoxysuccinimidato (2), and (η5-cyclopentadienyl)Ru(CO)2-N-phthalimidato (3). We studied the effects of ruthenium complexes 1–3 at a low concentration of 50 µM on the viability and the cell cycle of peripheral blood mononuclear cells (PBMCs) and HL-60 leukemic cells exposed to oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Wang et al ( 2022) [158] reported on the study of four polypyridyl Ru(II) complexes (56-59) as bifunctional TAR RNA binders and HIV-1 reverse transcriptase (RT) inhibitors. Molecular recognition of the hydrogen bonds further stabilized the Ru(II)-RNA-bound Wang et al (2022) [158] reported on the study of four polypyridyl Ru(II) complexes (56)(57)(58)(59) as bifunctional TAR RNA binders and HIV-1 reverse transcriptase (RT) inhibitors. Molecular recognition of the hydrogen bonds further stabilized the Ru(II)-RNA-bound system through electrostatic attraction, which efficiently inhibited the Moloney murine leukemia virus (M-MuLV) and HIV-1 RTs.…”
Section: Preclinical In Vitro Studies and In Silico Studies On Ru(ii)...mentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al ( 2022) [158] reported on the study of four polypyridyl Ru(II) complexes (56-59) as bifunctional TAR RNA binders and HIV-1 reverse transcriptase (RT) inhibitors. Molecular recognition of the hydrogen bonds further stabilized the Ru(II)-RNA-bound Wang et al (2022) [158] reported on the study of four polypyridyl Ru(II) complexes (56)(57)(58)(59) as bifunctional TAR RNA binders and HIV-1 reverse transcriptase (RT) inhibitors. Molecular recognition of the hydrogen bonds further stabilized the Ru(II)-RNA-bound system through electrostatic attraction, which efficiently inhibited the Moloney murine leukemia virus (M-MuLV) and HIV-1 RTs.…”
Section: Preclinical In Vitro Studies and In Silico Studies On Ru(ii)...mentioning
confidence: 99%
“…With these activities, Ru can help to trigger antitumor activity only in desirable areas of the body or in cancer cells, apart from classical chemotherapeutic action [56,57]. Over the last two decades, the complexes of ruthenium have been also studied for their antioxidant [58], antimicrobial [59], and antiviral activities [60,61]. Moreover, the modulation activity of amyloid-β aggregation has been described, which can be useful in the treatment of Alzheimer's disease [62,63].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many investigations have recorded the antioxidant properties of succinimide and sulphonyl moieties. A few examples are as follows: ruthenium complexes with succinimide ligands act against HL-60 leukemic cells and PBMCs, 26 the antioxidant potential of aldehydic-pyrrolidinedione against free radicals (ABTS, DPPH, and H 2 O 2 ), 1 the antioxidant property of ketoesters derivatives allow them to be used as supplements for the treatment of Alzheimer's disease, 12 sulfonyl ester-based heterocyclic Schiff bases against β-carotene linoleic acid and CUPRAC assays, 27 and bis(aroyl/arylsulfonyl ethene sulfonyl methyl azolyl)pyridine 28 and N -[(2-arylmethylthio)phenylsulfonyl] cinnamamide 29 against free radicals. Antibacterial studies of succinimide and sulphonyl moieties have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…1 Until today, a wide range of different ligands has been chelated to ruthenium, such as Schiff bases, hydrazones, thiosemicarbazones, succinimidato, and phthalimidato ligands, and even flavonoids, as the pharmacological properties of metal complexes depend on both the metal ion and the ligand. 3,4 Schiff bases are widely used due to their thermal and chemical stability, and their simple synthesis. 5 Alone, or bound to metal-ions, Schiff bases are used in many branches of chemistry, including inor-ganic, organic, polymer chemistry, industrial chemistry, but also in material science and pharmacological studies.…”
Section: Introductionmentioning
confidence: 99%
“…8 Recently, several in vitro studies have investigated ruthenium complexes containing diverse ligands for their radical scavenging activity, and compared to a range of standard antioxidant substances, such as ascorbic acid, alpha-tocopherol or butylated hydroxytoluene. 4,[6][7][8][9][10][11][12] A few in vivo studies have also been performed, reporting excellent antioxidant properties of ruthenium complexes that reduced intracellular levels of reactive oxygen species. 13 Mechanistic studies have shown that Ru(III) complexes are more inert in physiological conditions but are, nevertheless, readily reduced to Ru(II) in the acidic, glutathione-rich environment of cancerous cells, thus making water-soluble Ru(III) complexes the preferred targets for the synthesis of bioactive metallodrugs.…”
Section: Introductionmentioning
confidence: 99%